Why do firms hold so much cash? A tax-based explanation - Fritz Foley, C.; Hartzell, Jay C.; Titman, Sheridan; Twite, Garry (Journal of Financial Economics, 2007)
US corporations hold significant amounts of cash on their balance sheets. This paper develops and tests the hypothesis that the magnitude of US multinational cash holdings are, in part, a consequence of the tax costs associated with repatriating foreign income. Consistent with this hypothesis, firms facing higher repatriation taxes hold higher levels of cash, hold this cash abroad, and hold this cash in affiliates that trigger high tax costs when repatriating earnings. In addition, less financially constrained firms and those that are more technology intensive exhibit a higher sensitivity of affiliate cash holdings to repatriation tax burdens.